The Effect of Cultivation Age on The Carginan Content of Seaweed (Kappaphycus alvarezii) in Beach of Ekas, Lombok Timur District - Rifaid, Rifaid; Cokrowati, Nunik; Scabra, Andre Rachmat (Jurnal Media Akuakultur Indonesia, 2023)
West Nusa Tenggara Province has potential seaweed resources. This study aims to analyze the yield of carrageenan at different cultivation ages. West nusa tenggara province has an area for seaweed cultivation of 25,206.6 ha. The area is spread over the districts of East Lombok, west Lombok, central Lombok, Sumbawa, Dompu, Bima, the city of Mataram, the city of Bima, west Sumbawa and north Lombok. Seaweed is a chlorophyll plant and is classified as a low-level plant that has no true roots, stems or leaves, but only resembles a stem called a thalus. This research was conducted in Ekas Bay, Ekas Buana Village, Jerowaru District, East Lombok, and West Nusa Tenggara. This study used a completely randomized design (CRD) with 4 treatments: P1: 15 days, P2: 25 days, P3: 35 days, and P4: 45 days. The yield of K. alvarezii carrageenan obtained the highest score in treatment (P4), which was 53.4%. The chlorophyll content of K. alvarezii seaweed obtained the highest value in treatment (P4), namely 5.1 mg/L. Based on the results of research data analysis, it was found that the different cultivation ages of Kappaphycus alvarezii had a significant effect on absolute growth, specific growth and no significant effect on carrageenan content. In this study, the P4 treatment (45 days) obtained an absolute growth of 149 g, a specific growth of 5.46%, and a carrageenan content of 53.4%, and the best chlorophyll content value was 5.1 mg/L. The conclusion of this study is the best maintenance in this study, namely treatment P4 (45 days) obtained absolute growth of 149 grams, specific growth of 5.46%, and carrageenan content of 53.4%, and the best value of chlorophyll content is 5.1 mg /l.